CONTROLE E ACIONAMENTO UTILIZADO PARA SISTEMAS DE IRRIGAÇÃO (PIVÔ-CENTRAL) - Salvadori, Fabiano; Leandro, Gideon; Rech, Cassiano; Bolacell, Julio; Campos, Maurício d. (Salão do Conhecimento, 2013)
Resumo